Hybrid Based Substrate Modeling of MOSFET: A Review - Charu Dua; Jyoti Sehgal; Rajiv Sharma (Journal of Power Electronics and Devices, 2016)
A comparative study of different substrate materials has been done. In this paper, we have focused on the SiGe MOSFET and Hybrid MOSFET. The extraordinary characteristics of both MOSFETs make them a promising candidate for applications in MOS transistors. The effect of wide range of temperature has also been studied for different substrate materials.